The higher education funding formula review process: Best practices. Issue 198 (14th September 2022) - Pinkard, Jim; Weeden, Dustin; LaBruyere, Matthew; Collins, Crystal L.
Abstract: This chapter describes a comprehensive set of best practices for the evaluation of state formula funding models and state higher education funding in general, based on existing practices within the United States. It represents a review of practices that lead to stakeholder engagement as an objective, collaborative process.